THE INFLUENCE OF THE INTEGRATED INQUIRY LEARNING MODEL (SCIENCE AND THE QUR'AN) ON STUDENTS' COGNITIVE LEARNING OUTCOMES - Monika Dwi Anggita; Adrian Topano; Deni Febrini (Universitas Bhinneka PGRI, 2024)
This research is motivated by the lack of use of a variety of learning models, teachers only rely on books, so the learning process mostly takes place only using the lecture method, so students are not actively involved in learning. Science learning does not display the typical characteristics of the integration of science and the Koran as conveyed in the 2013 curriculum, there is still no formal implementation of this in the learning process. This research aims to determine whether there is an influence of the integrated inquiry learning model (science and the Koran) on students' cognitive learning outcomes in Integrated Science learning on the subject of the Solar System. The type of research is quantitative research with a quasi-experimental approach method. The research design used was a control group pretest and posttest design. The population in the research were all students of class VII SMPN 12 Bengkulu City and sample in this study was 60 students consisting of 30 control class students (class VII C) and 30 experimental class students (class VII D). Data collection techniques in this research used observation, interviews, test questions and documentation. The instrument used in the research was a multiple choice test with a total of 40 questions. The results of the research show that there are differences in the cognitive learning outcomes of experimental class students with those in the control class with a posttest score of 82.08 75.08 and with a significance level (2 tailed) 0.05 with a value of 0.01.